Evidence for high breakpoint variability in 46, XX, SRY‐positive testicular disorder and frequent ARSE deletion that may be associated with short stature. (7th September 2022) - Capron, Céline; Januel, Louis; Vieville, Gaëlle; Jaillard, Sylvie; Kuentz, Paul; Salaun, Gaëlle; Nadeau, Gwenaël; Clement, Patrice; Brechard, Marie Pierre; Herve, Bérénice; Dupont, Jean Michel; Gruchy, Nicolas; et al.
Abstract: Background: The translocation of SRY onto one of the two X chromosomes results in a 46, XX testicular disorder of sex development; this is supposedly because of non‐allelic homologous recombination between the protein kinase X gene ( PRKX ) and the inverted protein kinase Y pseudogene ( PRKY ). Although 46, XX SRY ‐positive men are infertile, the literature data indicate that some of these individuals are of short stature (relative to the general population). We sought to determine whether short stature was linked to additional, more complex chromosomal rearrangements. Methods: Twelve laboratories gathered detailed clinical, anthropomorphic, cytogenetic and genetic data (including chromosome microarray data) on patients with 46, XX SRY ‐positive male syndrome. Results: SRY was present (suggesting a der(X)t(X;Y)) in 34 of the 38 cases (89.5%). When considering only the 20 patients with chromosome microarray data, we identified several chromosomal rearrangements and breakpoints, especially on the X chromosome. In the five cases for whom the X chromosome breakpoint was located in the pseudoautosomal region, there was partial duplication of the derivate X chromosome. In contrast, in the 15 cases for whom the breakpoint was located downstream of the pseudoautosomal region, part of the derivate X chromosome had been deleted (included the arylsulfatase E [ ARSE ] gene in 11 patients). For patients with versus without ARSE deletion, the mean height was, respectively, 167.7 ± 4.5 and 173.1 ± 4.0 cm; this difference was not statistically significant ( p = 0.1005). Conclusion: Although 46, XX SRY ‐positive male syndromes were mainly because of imbalanced crossover between the X and Y chromosome during meiosis, the breakpoints differed markedly from one patient to another (especially on the X chromosome); this suggests the presence of a replication‐based mechanism for recombination between non‐homologous sequences. In some patients, the translocation of SRY to the X chromosome was associated with ARSE gene deletion, which might have led to short stature. With a view to explaining this disorder of sex development, whole exome sequencing could be suggested for SRY ‐negative patients.